MOLECULAR STUDIES IN THE GENUS IRIS L.: A PRELIMINARY STUDY - TILLIE, N.; CHASE, M. W.; HALL, T. (Annali di Botanica, 2000)
Preliminary analyses of molecular sequence data from rps4 and trnL-F are presented. The results accord well with previous thinking about groupings within Iris. Several species generally accepted as distinct genera, Belamcanda, Pardanthopsis and Hermodactylus, fall within the genus Iris. Scorpiris also falls within Iris and should not be considered a separate genus. The series Sibiricae could be divided into two groups, Sibiricae and Chrysographes. Iris kolpakowskiana is closely related to subgenus Xiphium, and I. anguifuga belongs to series Tenuifoliae.